Penanganan Stunting Melalui Program Infak Telur di Kelurahan Tegalrejo - Rika Fadhiilah Az-zahra; Amin Yusuf (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This study examines the implementation of the Infak Telur program in Tegalrejo Village to address stunting issues. The program involves egg donations from the community, which are then distributed to needy families, especially those with young children. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The sources of data used by the researcher are primary and secondary data. The findings indicate that the program successfully increased protein and nutritional intake among children and received positive responses from the community and GenRe youth. Active community participation in the planning, implementation, and monitoring of the program was key to its success. The study suggests the need for ongoing support and coordination among relevant stakeholders to enhance the program's long-term effectiveness.